Financial Statement Fraud in Construction Companies: A Perspective of the Hexagon Fraud Theory - Mahardika, Ratu Persada Pahlevi Pasca; Warsito Kawedar (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
Fraud in financial statements refers to the deliberate manipulation of information to mislead stakeholders, often occurring in companies facing high external pressure and ambitious financial targets. This study aims to analyze the influence of the Hexagon Fraud Theory on financial statement fraud in construction companies listed on the Indonesia Stock Exchange (IDX) during the 2018–2022 period. Using a quantitative method with descriptive analysis and multiple linear regression, the study sampled construction companies selected through purposive sampling based on annual reports. Secondary data were collected through empirical and literature studies, then analyzed using descriptive statistical tests, classical assumption tests, and hypothesis testing to examine variable relationships using SPSS. The results show that external pressure, financial targets, the nature of the industry, external auditor quality, changes in auditors, changes in directors, and arrogance significantly influence fraud. In contrast, financial stability, ineffective monitoring, and the status of a company as a state-owned enterprise (SOE) are not significant. These findings highlight the importance of strict oversight of specific factors in the construction industry, such as external pressure and the industry's nature, as well as improving governance quality to prevent financial statement manipulation. The implications of this study suggest that construction companies need to enhance supervision and governance related to external pressure, financial target achievement, and the unique characteristics of the industry. Furthermore, prioritizing the quality of auditors and management of changes is essential to minimize the risk of financial statement manipulation.